The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1177/0363546512442336
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Injuries to the Anterior Cruciate Ligament in National Collegiate Athletic Association Football

Abstract: Between 2004 and 2009, NCAA football players experienced a greater number of ACL injuries in games compared with practices, in scrimmages compared with regular practices, and when playing on artificial turf surfaces. This latter finding will need to be confirmed by additional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
78
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 26 publications
6
78
1
Order By: Relevance
“…Knee-sprain rates were also higher in competition than in practice at each competition level. This finding is consistent with the results of previous injury-surveillance studies that identified higher competition injury rates in high school athletics, 22 collegiate athletics, [23][24][25] professional football, 26 and professional soccer. 27,28 The observation highlights the increased intensity of game play that may occur within competitions versus practices.…”
Section: Overall Frequencies and Ratessupporting
confidence: 92%
“…Knee-sprain rates were also higher in competition than in practice at each competition level. This finding is consistent with the results of previous injury-surveillance studies that identified higher competition injury rates in high school athletics, 22 collegiate athletics, [23][24][25] professional football, 26 and professional soccer. 27,28 The observation highlights the increased intensity of game play that may occur within competitions versus practices.…”
Section: Overall Frequencies and Ratessupporting
confidence: 92%
“…22 Sports such as soccer, football, and skiing have been reported to be high-risk sports and individuals who participate in these sports are 10 times more likely to rupture the ACL when compared to other sport activities. 23 Even though reconstruction is the most common treatment for ACL rupture, there remains debate in the literature regarding the optimal timing of surgery. 24 Smith et al concluded from their systematic review that there were no differences in clinical outcomes between early (less than 3 weeks) and delayed (greater than 6 weeks) ACL reconstruction (ACLR); however, their conclusion is based on present literature that has limitations, such as non-randomization and lack of appropriate blinding.…”
Section: Discussionmentioning
confidence: 99%
“…INTRODUCTION S PORT and physical activity have important cardiovascular, musculoskeletal and mental health benefits and are enjoyed by large numbers [1]. However, associated lower body musculoskeletal injuries are very common [2], [3], [4]. Almost all injuries are caused by relative excessive loading on the tissues i.e.…”
mentioning
confidence: 99%
“…joint angle and angular velocity) and some measure 1 of loading on their body (e.g. impact accelerations) 2 during a series of actions common to their sport and known to be related to injury (e.g. running [3], jumping and landing [6], agility cuts [9]).…”
mentioning
confidence: 99%
See 1 more Smart Citation